OPTIMALISASI KINERJA SDM MELALUI BUDAYA ORGANISASI DAN KOMITMEN SERTA MOTIVASI - Dian Rakasiwi; Ken Sudarti (Jurnal Ekonomi dan Bisnis, 2016)
ABSTRACTThis study examined the influence of organizational culture and commitment also motivation tooptimize employee performance. From the previous studies there are research gaps where therelationship between organizational culture and commitment to the employee performance isinconsistent. Researcher interested in testing the motivation as an intervening variable betweenorganizational culture and commitment to employee performance where the existing researchmore studied about commitment as intervening between organizational culture and motivationon the employee performance. Researcher using random sampling with 110 samples. The dataanalysis technique in this study is used regression and path analysis with SPSS 22. The entiretyof the hypothesis is proven significantly. From the research gaps results of this study supportthe results were positive influence between organizational culture and commitment to employeeperformance. Organizational culture and the commitment also motivation affecting employeeperformance of 81.7%, while the rest influenced by other variables. Based on path analysismotivation in this study can not be intervening between organizational culture and commitmentto employee performance. Optimizing the performance of CV Perkasa Telkomselindo will bemore effective if it is through direct sowing culture of the organization and the commitment alsomotivation than a third confounding variables.Keywords: Commitment, Employee Performance, Motivation, Organizational Culture